The Mediating Role of Metacognition in the Relationship between Self-efficacy and Self-handicapping on Academic Achievement among University Undergraduates - Arslan Khalid,; Khizra Iqbal,; Abdul Sattar Ghaffari,; Sahar Mughal,; Malik Mureed Hussaian, (Al-Qanṭara, 2023)
Academic success is one of the most critical challenges and concerns in academic institutions as well as in student's life, as different factors are contributing to this process. This study aimed to determine the impact of self-efficacy and self-handicapping behavior mediated by metacognition on academic achievement. The sample included 271 (male=109 and female=162) university students' approach from Islamia University of Bahawalpur, both main and sub-campus, through random sampling technique to collect data. The period of study was from January 2023 to May 2023. The assessment included the self-efficacy scale, the academic self-handicapping scale, and the cognitive and metacognitive strategies scale were used in the study. Academic achievement was measured through the CGPA of students. For results analysis, descriptive (frequency, percentage, and mean) and inferential statistics (Pearson correlation, mediation path analysis, and t-test were applied. Findings of the path analysis showed the partial mediating effect of metacognition on self-efficacy and academic achievement. They showed a total effect on self-handicapping behavior and academic achievement among students. Keywords: Self-efficacy, Self-handicapping, Metacognition, Academic Achievement, Students